Pengaruh Sikap, Efikasi Diri, dan Karakteristik Wirausaha terhadap Minat Berwirausaha Mahasiswa - Weka Apsari Maala Nuhlasita; Ruri Nurul Aeni Wulandari (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2022)
This study aims: (1) to analyze how the influence of attitudes on students' interest in entrepreneurship, (2) to analyze how the influence of self-efficacy on students' interest in entrepreneurship, (3) to analyze how the influence of entrepreneurial characteristics on students' interest in entrepreneurship, (4) to analyze how the influence of attitudes, efficacyself, and entrepreneurial characteristics simultaneously on interest in entrepreneurship in office administration education study program students.This research is a descriptive quantitative study conducted on students of the 2018 and 2019 Unesa office administration education program with a total population and sample of 115 students.Based on the results of the study, it shows that: (1) attitude has no influence on interest in entrepreneurship, (2) Self-efficacy has an influence on interest in entrepreneurship (3)Entrepreneurial characteristics have an influence on interest in entrepreneurship, (4) Attitudes, self-efficacy and entrepreneurial characteristics have a joint effect on interest in entrepreneurship